Waqf Land in Madura; Its Management and Typical Dispute Resolution - Rudy Haryanto; Lailatul Maufiroh; Sulaiman, Sulaiman Hasan (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
The abundant waqf practice does not always come with good management which leads to the emergence of conflicts. Conflicts over waqf land are easy to find, including those that occurred in Pangereman Village, Ketapang District, Sampang Regency, East Java Province. This research aims to explore the waqf land practice and management, the conflict or dispute, and its resolution according to Islamic and Indonesian positive law. The method used is descriptive qualitative by connecting the theories and problems of Islamic and Indonesian positive law. Data was obtained through observation and in-depth interviews with nāẓir, wāqif, wariṡah wāqif, village heads, and religious figures. Researchers also observed the situation of the village and the current condition of the conflict. The results of this research are: 1) the waqf land practices had occurred in a cultural way and the village government is the one who manages it; 2) the conflict was due to the absence of waqf transaction official note while the waqf land was not used anymore. This situation led to the heir of wāqif wanted to take the waqf land back; 3) Conflict resolution through traditional ways (deliberation and mediation) was proved to be effective. The role of kiai as a trustworthy one did matter. Although the litigation way was not used, it showed the same spirit as what Indonesian positive law coveys about conflict resolution.